2021
DOI: 10.3390/diagnostics11060974
|View full text |Cite
|
Sign up to set email alerts
|

Colonic Volume Changes in Paediatric Constipation Compared to Normal Values Measured Using MRI

Abstract: Background: Functional constipation in children is common. Management of this condition can be challenging and is often based on symptom reports. Increased, objective knowledge of colonic volume changes in constipation compared to health could provide additional information. However, very little data on paediatric colonic volume is available except from methods that are invasive or require unphysiological colonic preparations. Objectives: (1) To measure volumes of the undisturbed colon in children with functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 32 publications
3
13
0
Order By: Relevance
“…In agreement with a previous studies, we found that patients with FC had significantly longer colonic transit times (median 4.9 days) than those with IBS‐C (median 1.8 days) 17,28 . A recent study in pediatric constipated patients found a positive correlation between whole gut transit times and colonic volume 15 . Colonic transit times have significant interindividual and day‐to‐day variation.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In agreement with a previous studies, we found that patients with FC had significantly longer colonic transit times (median 4.9 days) than those with IBS‐C (median 1.8 days) 17,28 . A recent study in pediatric constipated patients found a positive correlation between whole gut transit times and colonic volume 15 . Colonic transit times have significant interindividual and day‐to‐day variation.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, semi‐automatic detection techniques reduce the time for otherwise comprehensive data analysis. Earlier studies have concluded that patients with constipation have larger colonic volumes than HC 14‐16 . Also, a previous study found that patients with FC had larger colonic volume than patients with IBS‐C, especially within the ascending colon 17 .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The median total colonic volume (TCV) of healthy children aged 14–18 years is reported to be 227 mL (interquartile range 180 mL–263 mL) [ 53 ], whereas the mean healthy adult TCV is 760 mL (with a 95% confidence interval of 662 mL–858 mL) [ 27 , 54 ]. Similarly, the length of the colon increases with age, from 52 cm length in children younger than 2 years of age to 150 cm in adults [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…This would represent 525–600 mg (NOAEL) or 5.3–6 mg (ADI) of glyphosate in feces for an infant (15 kg). Considering colonic volume of healthy infants around 0.2 L (Sharif et al, 2021), NOAEL levels of glyphosate could represent 2,625–3,000 mg/L in feces, and ADI levels of glyphosate 100-time lower values. We used 100 mg/L, a dose in between these two reference values.…”
Section: Discussionmentioning
confidence: 99%